Exploring The Future Of Health Through The Selr Mathematical Model With The 4th Order Pertubation Homotopy Method On The Risk Of Diabetes Among Mathematics Students Of Fmipa Unm Due To Unhealthy Lifestyles - Side, Syafruddin; Sanusi, Wahida; Pandjajangi, Andi Muhammad Ridho Yusuf Sainon Andi (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2025)
This study aims to obtain a numerical solution of the Susceptible-Exposed-Latent-Recovered (SELR) model with a delay time for diabetes cases among active students of FMIPA UNM. This SELR model is built based on certain assumptions, then an analysis is carried out to determine the stability of the model, and simulations are carried out to predict the incidence rate of diabetes. This study is an applied research, and the method used to obtain a numerical solution of the SELR model is the 4th Order Homotopy Perturbation Method, using secondary data. The results of this study include a numerical solution of the SELR model for diabetes cases with the Homotopy Perturbation Method, which shows that this model can predict the potential spread of diabetes among students.